Beyond the 'extinction of experience' – Novel pathways between nature experience and support for nature conservation. (March 2019) - Dean, Angela J.; Barnett, Adrian G.; Wilson, Kerrie A.; Turrell, Gavin
Graphical abstract: Highlights: Activity in parks and on beaches is associated with support for conservation. Proximity to rivers, but not coasts or parks, was linked to conservation support. These effects are not specific to nature: exercise also elicited support. Environmental concern only mediated the pathway between activity in parks. Wellbeing and social interaction were key pathways between experience and support. Abstract: It is argued that loss and degradation of natural ecosystems reduce the opportunity to experience nature, and as a consequence, reduce concern for nature and support for nature conservation. This phenomenon is termed the 'extinction of experience'. Research suggests a potential association between some nature experiences and conservation support. However, the influence of more typical urban nature experiences on conservation support—such as visiting urban parks—is not well understood. We used a longitudinal, representative dataset of adults in Brisbane, Australia (N = 6181) and examined the effects of nature experiences on conservation support using data from the same individuals surveyed at two time periods (2009 and 2011). Frequency of park use for physical activity with others was associated with conservation support, but no effects were observed for proximity to parkland or area of parkland adjacent to home. Frequency of physical activity on beaches and proximity to waterways were both associated with stronger conservation support, but coastal proximity was associated with lower conservation support. Mediation analysis examined how these experiences elicited support. The influence of park use on conservation support was mediated by all three tested pathways: environmental concern (as theorized by the extinction of experience), and two novel pathways, wellbeing, and social interactions. Neither beach use nor proximity to waterways elicited their effects via environmental concern; the effect of beach use was mediated by wellbeing and social interactions, whereas the effect of waterway proximity was mediated by wellbeing only. To assess whether observed effects were specific to nature, we examined the influence of two contrasting experiences on conservation support: both frequency of exercise classes and weights training elicited conservation support. Although certain urban nature experiences may elicit conservation support, results suggest that a variety of life experiences influence an individual's capacity to support environmental initiatives. Rather than diminishing the role of nature, we argue these findings identify diverse entry points for broadening community support for nature conservation.